Industrial training report: My Fimedia Network Technology Sdn. Bhd. / Nur Emylia Ezzati Na’aimi - Na’aimi, Nur Emylia Ezzati (Faculty of Business and Management, 2025)
My final semester obligation is to finish MGT666, which is an Industrial Training program. I effectively completed my internship at My Fimedia Network Technology Sdn. Bhd., typically referred to as Skintific, which is located in Menara Binjai in Kuala Lumpur, for a period of approximately five months and twelve days. The internship began on August 12, 2024, and lasted until January 24, 2025. This report provides an in-depth review of my five months and twelve days of internship at Skintific which is in the industry of Health and Personal Care Products. The focus of this report is to highlight my life goals, experiences, abilities, and personal development. My intensity of focusses will help me become a person of greater integrity. Regarding my internship at Skintific, I work in the Content Department as a Marketing Administrator. My primary responsibility is to manage the video substances on my TikTok social media channels. This includes uploading videos, scheduling their release times, creating captions, generating interactions with audiences, and measuring their performance using analytics. Indeed, I carried out all my tasks proficiently. Lastly, I ought to say that I believe doing an internship at Skintific is a great opportunity. My comprehension of the company's business is expansive. Throughout this experience, I am able to develop my technical and interpersonal skills and get valuable insight about how a successful organisation in the beauty and wellness industry operates. I sincerely appreciate the opportunity for me to join and gain knowledge in such a dynamic environment.